RETRACTED : The Influence of Product Quality, Brand Image and Advertising on The Purchase Decision of Honda Mobilio in South Jakarta - Fitriyanto; Herry Krisnandi; Kumba Digdowiseiso (Journal of Social Science, 2024)
This study aims to analyze the effect of product quality, brand image and advertising on the purchasing decisions of Honda Mobilio in South Jakarta. The method used in this research is descriptive quantitative with the population in this study are users of Honda Mobilio in South Jakarta. The sampling technique in this study was purposive sampling and quota sampling. The samples used in this study were 100 respondents with the criteria of Honda Mobilio car consumers who had bought and used for at least 1 year. The data in this study used primary data by distributing questionnaires which were processed using Statistical Package for the Social Science software (SPSS 23.0). The data analysis technique used is multiple linear regression analysis. The results of this study indicate that (1) Product Quality Variable (X1) has a positive and significant effect on Purchasing Decisions (Y). (2) Brand Image Variables (X2) have a positive and significant effect on Purchasing Decisions (Y). (3) Advertising (X3) Variables (X3) have a positive and significant effect on Purchasing Decisions (Y).